A Review of Some Recent Studies on Buoyancy Driven Flows in an Urban Environment. (25th September 2014) - Hajra, Bodhisatta
Abstract : This paper reviews some recent studies (after 2000) pertaining to buoyancy driven flows in nature and thier use in reducing air pollution levels in a city (city ventilation). Natural convection flows occur due to the heating and cooling of various urban surfaces (e.g., mountain slopes), leading to upslope and downslope flows. Such flows can have a significant effect on city ventilation which has been the subject of study in the recent times due to increased pollution levels in a city. A major portion of the research reviewed here consists of natural convection flows occurring along mountain slopes, with a few studies devoted to flows along building walls. The studies discussed here primarily include field measurements and computational fluid dynamics (CFD) models. This review shows that for densely populated cities with high pollution levels, natural convection flows (mountain slope or building walls) can significantly aid the dispersion of pollutants. Additional studies in this area using CFD and water channel measurements can explain the physical processes involved in such flows and help improve CFD modelling. Future research should focus on a complete understanding of the mechanisms of buoyancy flows in nature and developing design guidelines for better planning of cities.